Behind a Professional Smile: The Influence of Perceived Organizational Support on Emotional Labor in Hospitality Industry - Alifah, Syifana Nur; Prihastuty, Rahmawati (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The hospitality industry in big cities faces tight competition in providing excellent service. As a part that is intense in serving guests, the front office is required to display emotions according to the company's display rules, this process is called emotional labor. However, it is not always easy to do, especially when there are events that disturb the mood. Perceived organizational support (POS) as one of the source affective events can affect employees' affective state at work. Based on the problem, this study intends to determine the influence of POS on emotional labor among front offices of 4- and 5-star hotels in Semarang. A total of 60 subjects were collected through purposive sampling. Data was analysed through instrument tests, classical assumption tests, and hypothesis test using simple linear regression analysis. The study showed that POS negatively influence emotional labor, with a p-value <0.05 and a contribution of 13.8%. The regression equation Y=27.96 -0.263X. This finding indicates that high POS can reduce the burden of emotional labor and affect the quality of service delivery to guests.